2006
DOI: 10.1002/mrd.20553
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oocyte maturation media on early bovine embryonic development

Abstract: Successful production of high quality blastocysts in vitro depends on the use of a culture system that ensures the acquisition of developmental competence by the maturing oocyte. It is now clear that the in vitro maturation environment has a major influence on the oocyte's ability to acquire the potential to develop into blastocysts. In this work we examine the impact of oocyte culture media on the quality of blastocysts by comparing developmental rates, cell number and their allocation to embryonic cell linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 81 publications
4
33
0
7
Order By: Relevance
“…Experimental evidence in both mice (90) and cows (91)(92)(93) demonstrated that the medium, its supplements, and other factors (e.g., the oxygen atmosphere) used for oocyte culture and maturation can influence mRNA expression and development of the resultant embryos. Owing to the striking similarities to human oocyte and embryo development, bovine oocytes may be a better model than murine for assessing the epigenetic risks of human ART.…”
Section: Epigenetic Effects Of Oocyte Culture and Maturationmentioning
confidence: 99%
“…Experimental evidence in both mice (90) and cows (91)(92)(93) demonstrated that the medium, its supplements, and other factors (e.g., the oxygen atmosphere) used for oocyte culture and maturation can influence mRNA expression and development of the resultant embryos. Owing to the striking similarities to human oocyte and embryo development, bovine oocytes may be a better model than murine for assessing the epigenetic risks of human ART.…”
Section: Epigenetic Effects Of Oocyte Culture and Maturationmentioning
confidence: 99%
“…During the process of oo-and folliculo-genesis, oocytes acquire normal morphology (high quality of oocytes as defined in Materials and Methods), the ability to resume meiosis, and, after ovulation, the ability to be successfully fertilized by a spermatozoon (Coticchio et al, 2004;Russell et al, 2006;Sirard et al, 2006). Moreover, the mature female gamete must undergo several cellular and molecular changes.…”
mentioning
confidence: 99%
“…While formation of the blastocyst is undoubtedly an important checkpoint/landmark on the developmental axis, it is important to remember that the blastocyst is the product of a sequence of events that precede it, as outlined above. Although not the main subject of this review, there is evidence to demonstrate that the environment to which the oocyte is exposed during maturation can influence the pattern of transcripts in the matured oocyte , Lonergan et al 2003 and in the resulting blastocyst (Russell et al 2006). However, most evidence suggests that the pattern of mRNA abundance in the blastocyst, and the quality of the blastocyst in terms of establishing and maintaining a pregnancy, is dictated by the post-fertilization conditions of culture (Lonergan et al 2006).…”
Section: Impact Of Culture On Preimplantation Developmentmentioning
confidence: 98%